The relationship between the use of ICT and the feeling of loneliness: A look from the Social Determinants of Health of the elderly in Chile - Urbina Carreño, Alfredo (Revista Española de Comunicación en Salud, 2023)
Introduction: Since the arrival of COVID-19 in Chile, the older adult population's communication forms have changed, generating effects on their health due to digital social exclusion. Objective: To demonstrate the problems and causes of the lack of excellent connectivity and social communication among older people in Chile, according to their use of and access to ICT, and their effect on loneliness, considered a public health problem. Methodology: Descriptive study through a literature review on the relationship between using ICT, loneliness in older people and the possible effects on health. The Health Determinants Theory was used to explore this relationship. Results: The problems and causes focus on structural determinants, specifically the lack of digital social inclusion policies, educational differences, socioeconomic level and territory. These determinants intervene in using and accessing ICT, which could affect loneliness. Conclusion: A greater incorporation of public policies that are directly related to the digital social inclusion of this group in Chile, whose population density is increasing daily, is required.
Keywords: ICT; loneliness; older people; social determinants of health